Efektivitas Konseling Kelompok Pendekatan REBT dengan Teknik Disputing Terhadap Perilaku Mencontek Siswa Kelas Xl SMAK Hikmah Mandala (Jurnal Insan Pendidikan dan Sosial Humaniora, 2025)
Academic dishonesty, particularly cheating during examinations, remains a common issue among high school student and undermines the development of students integrity and responsibility. This study aims to determine the effectiveness of group counselling using the Rational emotive behaviour theraphy (REBT) approach with the disputing technique in reducing cheating behaviour among 11 grade students were selected throught purposive sampling and divided into experimental and control groups. The experimental group received eight sessions of group counselling integrating REBT and Socretes dialogue as the disputing technique. Data were analysed using paired sample t-test and independent sample t-test. The result indicated a significant desrease in cheating behaviour in the experimental group compared to the control group. The findings suggest that group counselling based on the REBT approach and disputing technique is effective in reducing students cheating behaviour. This study contributes to the development of character education strategis and prpvides pratical implications for school based counselling progams to foster academic integrity.